Risk Management, Working Capital Management and Financial Performance - Wisnu Panggah Setiyono; Lia Ernawati (Proceedings of The ICECRS, 2017)
Research Purposes: Aim of this study was to know the impact of Risk Management and Working Capital Management to The Financial Performance of Companies Listed In Indonesia Stock Exchange (IDX). Variables: This study employed Risk management proxied by Internal Audit. The proxies of working capital management, we used Current Ratio (CR) and Working Capital Turnover (WCTO). The Financial Performance we used Return On Assets (ROA) ratio as a proxy. Research Method: We used multiple linear regression analysis to analyzed whether the Risk management and the working capital management had impact on The Financial Performance. We also performed classical assumption tests including; normality test, multicolinearity, autocorrelation and heteroskesdasticity. Results: The results of this study indicate that simultaneously Internal Audit, CR and WCTO have a significant effect on financial performance. However, the partial effect had various results. The Internal audit and CR have no significant effect on financial performance whereas WCTO has a significant negative effect on financial performance.